A Study on Impact of Microfinance Through Self-Help Groups on Economic Empowerment of the Beneficiaries in Uttarakhand. - Gambhir, Sonia; Sahani, Deepak (International Journal of Psychosocial Rehabilitation, 2020)
-Microfinance has enabled the active poor to have access to all financial products which has never been utilized in the traditional financial system. Self- help Groups (SHGs) are meant to empower women both socially and economically. They encourage women to participate in decision making in the household and on social issues and prepare rural women to take up leadership positions. This paper sheds a light on the economic empowerment of the beneficiaries in Uttarakhand. The study has been undertaken by collecting the primary data from 507 SHGs members from three districts of Uttarakhand. The study helps in explaining the impact of microfinance in economic empowerment of the members in State of Uttarakhand.